1997
DOI: 10.1074/jbc.272.23.14509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a 20.8-kDaSchistosoma mansoni Antigen

Abstract: Survival of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…In fact, expression of Sm21.7 appeared to be relatively constant throughout those life stages present in the host, whereas expressions of Sm22.6 and Sm20.8 were mostly concentrated in the adult worm. Earlier expression studies, although not entirely consistent, do support our findings that transcription and translation of Sm22.6 and Sm20.8 are high in adult worms and absent in eggs [11, 13, 16, 33]. Furthermore, the ubiquitous nature of Sm21.7 is supported by previous Northern blotting experiments on Sm21.7 [12] which showed that mRNA was equally abundant in snail-stage sporocysts, schistosomula and adult worms.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In fact, expression of Sm21.7 appeared to be relatively constant throughout those life stages present in the host, whereas expressions of Sm22.6 and Sm20.8 were mostly concentrated in the adult worm. Earlier expression studies, although not entirely consistent, do support our findings that transcription and translation of Sm22.6 and Sm20.8 are high in adult worms and absent in eggs [11, 13, 16, 33]. Furthermore, the ubiquitous nature of Sm21.7 is supported by previous Northern blotting experiments on Sm21.7 [12] which showed that mRNA was equally abundant in snail-stage sporocysts, schistosomula and adult worms.…”
Section: Discussionsupporting
confidence: 76%
“…M29837), Sm21.7 (M67507), Sm20.8 (U872430) and SmDLC1 (U55992) were cloned into pGEX-1λT expression vector (Pharmacia) as described previously [8, 13, 25]. The antigens were expressed as GST fusion proteins, cleaved and purified by preparative electrophoresis as described previously [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deduced amino acid sequence showed significant identity to several schistosome tegumental antigens which contain an EF–hand motif (aa 56–68), including Sm21.7 [24], Sm20.8 [25]and Sm16 [26]. Similar to earlier reports [12, 22], Sj22.6 also exhibited similarity to calmodulins, myosin regulatory light chains and other calcium–binding proteins.…”
Section: Resultssupporting
confidence: 67%